Penguatan Manajemen Evaluasi Diri Madrasah Pada KKM Kecamatan Kelapa Dua Tangerang - Muslim, Ahmad Buchori; Candra, Bach Yunof (STMIK Royal, 2024)
This service aims to analyze and understand the readiness of madrasahs in conducting madrasah self-evaluation and maximize the implementation of training and assistance in madrasah self-evaluation management in the Madrasah Ibtidaiyah Working Group, Kelapa Dua Tangerang District in order to increase understanding and skills in conducting madrasah self-evaluation in accordance with the indicators set in the e- RKAM application. The methods and techniques used in this service are training and mentoring at each madrasah targeted for service. The expected result in this service is the creation of effective madrasah self-evaluation management in the process of implementing madrasah self-evaluation which is carried out annually so that it can provide relevant information to madrasah residents and policymakers about the achievement of madrasah quality according to national education standards. The results that can be seen in this service are the improvement of madrasah quality as seen from the quality achievement performance score which increased by an average of 11% between 2021 and 2022.